2011
DOI: 10.1016/j.bbi.2010.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic neuronal injury in the adult rat brain following neonatal exposure to lipopolysaccharide and the silent neurotoxicity

Abstract: Our previous studies have shown that neonatal exposure to lipopolysaccharide (LPS) resulted in motor dysfunction and dopaminergic neuronal injury in the juvenile rat brain. To further examine whether neonatal LPS exposure has persisting effects in adult rats, motor behaviors were examined from postnatal day 7 (P7) to P70 and brain injury was determined in P70 rats following an intracerebral injection of LPS (1 mg/kg) in P5 Sprague-Dawley male rats. Although neonatal LPS exposure resulted in hyperactivity in lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
116
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(131 citation statements)
references
References 58 publications
(119 reference statements)
15
116
0
Order By: Relevance
“…Specifically, adult nLPS males who received exposure to a three-day stress protocol (restraint stress, isolation stress) spent less time in the open arms (exhibiting anxiogenic effect) compared to nLPS females and all other treatment groups (Walker et al, 2009). Lastly, Fan et al (2011) reported that nLPS (P5) male and female rats on P21 showed anxiolytic effects (spent more time in the open arms) on the EPM compared to nSal controls (Fan et al, 2011). The anxiolytic effects observed have been previously seen by others (Imhof et al, 1993;Masur et al, 1980;Walker et al, 2004).…”
Section: Neonatal Effects-existing Literature On the Effects Of Neonamentioning
confidence: 68%
See 3 more Smart Citations
“…Specifically, adult nLPS males who received exposure to a three-day stress protocol (restraint stress, isolation stress) spent less time in the open arms (exhibiting anxiogenic effect) compared to nLPS females and all other treatment groups (Walker et al, 2009). Lastly, Fan et al (2011) reported that nLPS (P5) male and female rats on P21 showed anxiolytic effects (spent more time in the open arms) on the EPM compared to nSal controls (Fan et al, 2011). The anxiolytic effects observed have been previously seen by others (Imhof et al, 1993;Masur et al, 1980;Walker et al, 2004).…”
Section: Neonatal Effects-existing Literature On the Effects Of Neonamentioning
confidence: 68%
“…Kohman et al found that nLPS (P4 and P5) treated male mice performed significantly fewer avoidance responses than saline treated males in a two-way active avoidance paradigm, a finding not observed in nLPS treated females on P70 (Kohman et al, 2008a;Kohman et al, 2008b). In another study however, no sex effects were detected on performance in a passive avoidance test in P21 rats administered LPS intracerebrally (1 mg/kg) on P5 (Fan et al, 2011). The authors found learning and memory deficits on this task in both nLPS males and females relative to nSal controls.…”
Section: Learning and Memorymentioning
confidence: 94%
See 2 more Smart Citations
“…One of the main alterations following perinatal infection/inflammation is a persistent low-grade inflammation characterized by higher expression of inflammatory mediators and also microglial reactivity during adulthood [236]. Adult rodent exposed during early-life to LPS-enhanced expression of CD11b, IL-1β and IL-6 and also more activated microglia in the hippocampus, the striatum and substantia nigra/ventral tegmental area [239,240]. This persistent low-grade inflammation sensitizes the brain to secondary injuries, which can lead to neurological disorders such as cerebral palsy, mood disorder, schizophrenia, or Parkinson disease [241].…”
Section: Linking Serotoninergic System and Neonatal Inflammation/ischmentioning
confidence: 99%